Hiperplasia endometrial cística e hidrossalpinge associada a cisto folicular em bovinos - Pereira, Jhonata V. T. N.; Pinho, Rogério O.; Meneses, Rodrigo M.; Mendes, Vívian R. A.; Pereira, Emílio C. M. [UNESP]; Pereira, Carlos E. R.; Guimarães, José D. (My University, 2015)
We report herein the occurrence of ovarian cysts, endometrial cysts and left hydrosalpinx in a bovine female. The diagnosis of such conditions was performed by rectal palpation and ultrasonography of the reproductive organs in addition to the correlation with hormone levels (estrogen and progesterone) in blood serum. Additionally, anatomical and histopathological examinations were performed post-mortem. In the right ovary extensive floating areas, corresponding to three major areas of anechoic 30 mm in diameter was detected by ultrasonography. This finding is characteristic of ovarian cystic structures, and was classified as follicular cysts, due to the absence of follicular luteinization wall. The determination of the concentration of estrogen (estradiol 17β) and progesterone in follicular fluid was performed by observing 44.8 ng/mL and 15.7 ng/mL, respectively, and in the serum 35.8 pg/mL and 0.2 ng/mL, respectively. In ultrassonographic assessment of the uterus was observed the presence of well-defined endometrium anechoic areas, indicating cystic formations, plus a small amount of liquid in the uterine lumen. A thickening of the wall and accumulation of fluid in the left uterine tube was also observed by ultrasonography and diagnosed as hydrosalpinx. Histologically, the cysts were classified as follicular cysts type I and changes in the uterus were consistent with cystic endometrial hyperplasia. In this case, the use of anatomical and hitopatological analyzes were useful to confirm the findings. However, the study shows that the conditions described can be diagnosed based solely on palpation and transrectal ultrasonography.
Cystic endometrial hyperplasia and hydrosalpinx associated with follicular cyst in cattle
Keywords: Endometrial cyst; Reproductive disorders; Ultrasonography